Endoscopic Cyanoacrylate Injection in the Management of Gastric Varices: Long-Term Safety and Efficacy - Raghavendran, Anand Kumar; Shetty, Shiran; Musunuri, Balaji; Rajpurohit, Siddheesh; Kumari, Preety; Nedunchezhian, Suriya; Shetty, Athish; Pai, C. Ganesh; Bhat, Ganesh (Journal of Digestive Endoscopy, 2025)
Despite endoscopic ultrasound-based endotherapy and radiologic intervention, endoscopic cyanoacrylate (E-CYA) injection still remain as commonly performed treatment modality for bleeding gastric varices (GVs) in real world. We analyzed the long-term safety and efficacy of E-CYA in bleeding GVs.In this retrospective analysis, patients who underwent E-CYA for GVs over the past 10 years were analyzed. The technical success, hemostasis rate, rebleeding rate, mortality rate, and procedure-related complications were analyzed. The predictive factors for a rebleed in terms of Child–Pugh status, the type, form, and size of GVs were computed.Of the 113, 96 (84.9%) met the inclusion criteria. The median follow-up was 30 (12–49) months. The mean age was 48.1 ± 6.1 years with most being male (83.3%, n = 80). The majority of them had cirrhosis (85.4%, n = 82). The technical success to achieve primary hemostasis was 98.9%. The median volume of glue to achieve hemostasis for each session was 2 (2–4) mL. At 1 month, 12 patients had a clinically significant rebleed (12.5%) and 6 (6.3%) had a rebleed at 6 months. At 1 and 6 months, 68.75% did not require further glue injection. The disease-related mortality was 10.41%. There was no procedure-related mortality.E-CYA injection shows excellent efficacy and long-term safety with low rebleeding rates and negligible procedure-related complications.
Keywords: gastric varices; glue injection; safety and efficacy